Acute undifferentiated febrile illness in a traveler returning from Burkina Faso, West Africa to Puducherry, India- a case report - Srikanth Srirama; Krishan Kumar Sihag; Anand Kumar Chandrasekaran; Neethi Prasannan Latha; Waseema Arif; Balaji Sampath Kumar; Panneer Devaraju (BMC Infectious Diseases)
Abstract Background Imported malaria remains a significant diagnostic challenge, particularly in regions approaching elimination. This case report is novel in its exploration of the complexities involved in diagnosing malaria imported from a high-endemic area to a low-endemic region, emphasizing the critical role of detailed travel history and molecular diagnostics in identifying the disease. The case underscores the potential public health implications of missing such diagnoses in regions where routine malaria testing is not performed due to low endemicity. Case presentation A 25-year-old male presented to a tertiary care hospital in Puducherry, India, with symptoms of intermittent fever, headache, loss of appetite, and vomiting, which persisted over a week. Initial laboratory findings showed thrombocytopenia and leukopenia, with negative tests for dengue, chikungunya, and scrub typhus. Further investigation using molecular diagnostic techniques identified Plasmodium falciparum. The patient had recently returned from Burkina Faso, West Africa, where he had experienced similar episodes of fever, establishing the diagnosis of imported malaria. Conclusions This case highlights the necessity of considering imported malaria in the differential diagnosis of febrile illnesses in India, a country nearing malaria elimination. It illustrates the importance of incorporating travel history into clinical evaluations and supports the use of molecular diagnostics to effectively diagnose malaria in settings where traditional diagnostic methods may overlook imported cases. The findings advocate for enhanced surveillance and diagnostic preparedness to manage imported cases of malaria, thereby supporting ongoing elimination efforts and preventing the re-establishment of local transmission. Clinical trial number Not applicable.